PENGARUH PENGELUARAN PEMERINTAH SEKTOR PENDIDIKAN, KESEHATAN DAN INFRASTUKTUR TERHADAP PERTUMBUHAN EKONOMI DAN PENINGKATAN PEMBANGUNAN MANUSIA DI PROVINSI KALIMANTAN TIMUR - Suparno, Heri (Journal of Innovation in Business and Economics, 2014)
The purpose of this research were: 1) determining the direct effect of government spending on education, health and infrastructure to economic growth and human development index, 2) investigating the direct impact of economic growth on the human development index, 3) describing the indirect consequence of government spending on the sector education, health and infrastructure to the human development index through economic growth. In order to examine the hypothesis testing, the researcher employed path analysis and used the data derived from government spending files which comprised the expenditures on education, health and infrastructure, human development index and economic growth from 1997 up to 2011. The analysis showed that there is a direct effect of government spending on education, health and infrastructure to the human development index and economic growth and indirect influences of the government expenditure on education, health and infrastructure to the human development index through economic growth